Relationships between vaccinations, herd introductions, and livestock losses in Northern Tanzania. (9th April 2022) - Ahmed, Haseeb; Yoder, Jonathan; de Glanville, William; Davis, Alicia; Kibona, Tito J.; Cleaveland, Sarah
Abstract: This article examines the relationships between livestock vaccinations, herd introduction decisions, and livestock disease–related outcomes. We develop a theoretical model and derive testable hypotheses about the relationships between these outcomes and practices and test them using two-stage least squares regression analysis. We find that vaccinations reduce disease-related livestock deaths, implying that vaccine availability and use may improve herd and household welfare. We do not find robust evidence of increase in disease-related illness due to herd introductions. Our results highlight the role of livestock vaccinations in safeguarding herd value, which is connected to broader household welfare for livestock keepers of Eastern Africa.